Des routes pour contrôler ? Aménagement des territoires de montagne et reconfiguration des mobilités au XIXe siècle - Emma-Sophie Mouret (Amnis)
The road planning of mountain areas can be thought of as a tool for social control in rural societies. In France, throughout the 19th century, the opening of roads on mountain areas took part in the state modernization planning of the countryside. The Vercors mountain range (Isère and Drôme departments) is a good example to analyse various links between roads planning and social control. During the 19th century, a suitable road network was built on the Vercors mountain range. The construction was managed by a regional agency : the Service Vicinal. The road network is organized according to an administrative model. It looks like a covering between high altitude areas, foothills and plains. The roads’ opening aims to manage and control inhabitant’s socio-economic uses. These should be compatible with the national economy during industrialization. At the same time, the State is looking to manage forest management. The road could be a strategic tool for preventing offence in public forest and movement’s norms are circulated by it. But the efficiency of the social control by roads is not perfect. Some failure could be observed if we asking for the local society to react to this. Who’s taking advantage of these ? Some socioeconomics gaps could have appeared ? Uses considered as offences are disappeared or are they modified ? What highlighted the socioeconomic impacts of road planning ?